Murder pays a call [large type] - Cohen, Nancy J., 1948- (Cohen, Nancy J., 1948- Keri Armstrong cozy mystery., 2026)
"When personal concierge Keri Armstrong swings by her favorite client's house to drop off groceries, she expects a heartfelt chat along with a cup of tea--not Fiona Sullivan dead in bed and her room ransacked. Though police chalk it up to a botched robbery, Keri isn't so sure. Whispers around town suggest Fiona wasn't as adored as Keri had believed, and many of the philanthropist's so-called friends in affluent Sunny Grove, Florida, seem glad she's gone. Keri refuses to let Fiona's memory be reduced to malicious gossip. Armed with a keen eye, insider access, and a fully charged tablet, she sets out to uncover the truth. Soon her file of suspects grows faster than her to-do list. Between sneaky neighbors, resentful relatives, and tight-lipped charity board members, Fiona left behind a trail of frenemies who'd happily compare notes at her memorial brunch. As Keri digs deeper, she discovers her late mentor had a gift for extracting people's secrets and using them like fine china--carefully storing them until they could serve a purpose. But Fiona also kept a few skeletons in her own walk-in closet. Now, with danger creeping closer, Keri must race to crack the case before her number comes up next . . . and Murder Pays a Call."--